Economic Effects of Covid-19 on Tourism Sector in Pakistan - Dr. Asma Akmal; Bisma Laeeque; Bakhtawar Mehar (Journal of Business & Tourism, 2021)
This research is done to ascertain the economic condition of the people of Pakistan during COVID-19 and the condition of tourism in the country. Despite of fact that travel bans were made along with school closure, however these hurdles did not affected tourism in Pakistan. The company’s balance sheet depicts more profit in comparison to previous years but that it is because of high fare and arrangement charges. Not due to increase in number of tourists. Purposive sampling strategy was used and the data was collected from pirvate travelling companies working in Pakistan. It is depicted by the results that the overall profit secured by the companies increased during corona (Mean profit before corona= 89666; Mean profit during corona = 102915). Furthermore the hypothesis was accepted that covid-19 positively effected tourism industry of Pakistan [p<.005; t=1.51 (df=23) SD= 43005.98].